2015
DOI: 10.1007/s11606-015-3315-5
|View full text |Cite
|
Sign up to set email alerts
|

Does Type 2 Diabetes Genetic Testing and Counseling Reduce Modifiable Risk Factors? A Randomized Controlled Trial of Veterans

Abstract: OBJECTIVE:We examined the clinical utility of supplementing type 2 diabetes mellitus (DM) risk counseling with DM genetic test results and counseling. RESEARCH DESIGN AND METHODS: In this randomized controlled trial, non-diabetic overweight/obese veteran outpatients aged 21 to 65 years received DM risk estimates for lifetime risk, family history, and fasting plasma glucose, followed by either genetic test results (CR+G; N = 303) or control eye disease counseling (CR+EYE; N = 298). All participants received bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 36 publications
4
57
0
1
Order By: Relevance
“…Of the 18 articles that assessed a nutrition-related outcome, 6 (33%) showed a positive, health-promoting effect of genetic testing on behaviour change at one or more time points (both short term and long term, as further outlined in Tables 1 and 2). While this does not indicate that the majority of studies positively influenced nutrition, multiple studies of good quality have demonstrated that it is possible to facilitate healthier nutritional behaviours through the provision of genetic testing [8, 9, 11, 46, 49, 51]. …”
Section: Resultsmentioning
confidence: 99%
“…Of the 18 articles that assessed a nutrition-related outcome, 6 (33%) showed a positive, health-promoting effect of genetic testing on behaviour change at one or more time points (both short term and long term, as further outlined in Tables 1 and 2). While this does not indicate that the majority of studies positively influenced nutrition, multiple studies of good quality have demonstrated that it is possible to facilitate healthier nutritional behaviours through the provision of genetic testing [8, 9, 11, 46, 49, 51]. …”
Section: Resultsmentioning
confidence: 99%
“…However, the volunteers tended to overestimate their risk at baseline and may therefore have been somewhat reassured by the information that they received, albeit not to the extent that they adopted unhealthy behaviors [46]. Nevertheless, we cannot exclude the possibility that provision of risk estimates that exceed participants’ perceived risk might influence behavior, although previous trials have not reported effects among high-risk subgroups [18,19]. Furthermore, it is possible that information concerning the genetic risk of diseases other than diabetes, such as various cancers or chronic neurodegenerative diseases, might elicit a greater response, although this has not been the finding of published trials [47].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, interpretation has been limited by risk of bias and additional differences between study groups than merely the provision of DNA-based disease risk information. Two recent trials report no behavioral impact of information about the genetic risk of type 2 diabetes [18,19]. However, neither included precise measures of behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In this well-designed randomized controlled trial conducted in a primary care setting, investigators analyzed three single nucleotide polymorphisms (SNPs) associated with diabetes risk to calculate the genetic risk for the intervention group and categorized their genetic risk as low, moderate, or high. They found that weight, insulin resistance, physical activity and perceived lifetime risk of diabetes did not differ between groups at 3 or 6 months.…”
mentioning
confidence: 99%